Autochthonomies : transnationalism, testimony, and transmission in the African Diaspora - Chancy, Myriam J. A., 1970- (New Black studies series., 2020)
"In this book of textual and cultural studies, Myriam J.A. Chancy focuses on the tropes of transnationalism, testimony and transmission within African diasporic texts. Not a work simply concerned with "racial rehabilitation" or "inclusion" within the dominant discourses of North America and Western Europe, it intends to serve as an intervention in race, Caribbean, African diasporic, and cultural studies by providing a radically new model for a culturally imbedded reading practice of contemporary works by African and African diasporic artists. Its purpose is to reveal the contributions to ontology that such artists deploy. In developing this approach, Chancy revisits the concept of "interpretive communities" from a distinctively African diasporic point of view. She uses concepts derived from contemporary philosophical approaches to subjectivity that revise-and mostly discard-Hegelian principles in order to assert less Eurocentric approaches. Building from these, she develops her neologism autochthonomy (aw-tok-ton-nuh-mee), which describes a practice of subjectivity and agency employed by African diasporic artists. Those artists chosen for this study bring together the experiences, movements, and knowledge of populations of African descent both on the continent and dispersed throughout Europe and the Americans in order to emphasize transnational interactions between African cultural producers and sites."--